Glandular trichome density and essential oil composition in leaves and inflorescences of Lippia origanoides Kunth (Verbenaceae) in the Brazilian Cerrado - Tozin, Luiz R. S. [UNESP]; Marques, Marcia O. M.; Rodrigues, Tatiane M. [UNESP] (Academia Brasileira de Ciências, 2015)
The essential oils from leaves and inflorescences of Lippia origanoides Kunth present aromatic and medicinal potential and have been used to treat several diseases, including melanoma. In Brazil, L. origanoides is commonly found in campo cerrado and cerrado stricto sensu, physiognomies featured mainly by the differential light conditions to which short and medium-sized plants are subjected. Our aim was to investigate the glandular trichome density and the yield and chemical composition of the essential oils in leaves and inflorescences of L. origanoides from campo cerrado and cerrado stricto sensu. For glandular density analysis, leaves and inflorescences were processed according to conventional techniques for scanning electron microscopy. The essential oils of leaves and inflorescences were obtained by hydrodistillation and identified with gas chromatography. Bracts and sepals showed the highest glandular density, followed by petals and leaves. The glandular density in the abaxial leaf surface was higher in individuals from the campo cerrado. In both populations the essential oil yield was higher in inflorescences than in leaves. The chemical composition of the essential oils varied among individuals from different areas and inside a same population. Our results demonstrated the chemical plasticity of L. origanoides suggesting the importance of monitoring its popular use.

Os óleos essenciais de folhas e inflorescências de Lippia origanoides Kunth apresentam potencial aromático e medicinal e têm sido utilizados no tratamento de diversas doenças, incluindo melanoma. No Brasil, L. origanoides é comumente encontrada no campo cerrado e no cerrado stricto sensu, fisionomias caracterizadas principalmente pelas diferentes condições de luminosidade às quais as plantas de médio e pequeno porte estão sujeitas. Nosso objetivo foi investigar a densidade de tricomas glandulares e o rendimento e a composição química do óleo essencial em folhas e inflorescências de L. origanoides do campo cerrado e do cerrado stricto sensu. Para análise de densidade glandular, folhas e inflorescências foram processadas segundo técnicas convencionais em microscopia eletrônica de varredura. Os óleos essenciais de folhas e inflorescências foram obtidos por hidrodestilação e identificados com cromatografia gasosa. Brácteas e sépalas mostraram a maior densidade glandular, seguidas por pétalas e folhas. A densidade glandular na face abaxial do limbo foliar foi maior em indivíduos do campo cerrado. Em ambas as fisionomias, o rendimento de óleos essenciais foi maior nas inflorescências em comparação com folhas. A composição química dos óleos essenciais variou entre os indivíduos de diferentes áreas e entre indivíduos da mesma população. Nossos resultados demonstraram a plasticidade química de L. origanoides sugerindo a importância do monitoramento de seu uso popular.
Keywords: Campo cerrado; Cerrado stricto sensu; External glands; Terpenes; Campo cerrado; Cerrado stricto sensu; Glândulas externas; Terpenos